Textual Revision and the Historicity of the Self: Some Factual Inaccuracies in The Prelude - Ahmed, Soheil (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
AbstractReading Wordsworth’s Prelude implicates us immediately in the politics of autobiographical writing — which deliberately elides, to use Felicity Nussbaum’s words, “the subject’s fragmentations and discontinuities.” But at the same time, one cannot help suspecting that the seemingly reasonable expectation of factual correctness in autobiography can also mask a deep denial of these essential fragmentations and discontinuities in the name of truth.Wordsworth’s revisions of the Prelude afford an insightful means of understanding these issues: here the imperatives of narrative self-constitution far outweigh the imperatives of literal facts. But the misdating of crucial events — such as the composition of the Glad Preamble — do not detract from its validity as autobiographical writing, but rather gives evidence of the self-problematising nature of origins. In fact, the interest in works such as the Prelude lies not in how closely they adhere to historical particularities, but how tenaciously their metaphoric transcendence resists reduction back to these historical particularities. Romantic subjectivity makes no clear distinction between self and the outer world of phenomena — and also it seems between self and self. This becomes abundantly clear in Wordsworth’s appropriation of Dorothy’s experience. In the Prelude this process is traceable eminently through the process of textual revisions as the present study argues.